The effect of environmental health education on microplastic pollution awareness - Mirac, Bayoglu Ahmet; Fatos, Uncu (Wiley, 2024)
Objective: The aim of this research is to investigate the effect of environmental health education given at the ninth-grade level on the microplastic pollution awareness level of students. Methods: This pretest-posttest experimental study with a randomized control group was conducted between 2022 and 2023 in three high schools in a province in eastern Turkey. The sample of the study consisted of 90 ninth-grade students (experimental group: 45, control group: 45), and the sample magnitude was determined by power analysis. Tools such as the Personal Information Form and Microplastic Pollution Awareness Scale (MPAS) were used to collect data. Training was given to the experimental group as a nursing intervention in a total of four sessions at 15-day intervals. No intervention was applied to the individuals in the control group. Results: While no significant difference was observed in the MPAS total score in the control group according to the pretest and posttest mean scores, a significant difference was observed in the MPAS total score in the experimental group (p < 0.05). When the posttest mean scores of the experimental and control groups were examined, it was observed that the posttest mean scores of the experimental group were higher than the posttest mean scores of the control group and there was a statistically significant difference (p < 0.05). Conclusion: It was observed that the microplastic pollution awareness level of the experimental group students who received environmental health training increased significantly. The issue of environmental health should be integrated into the education curriculum in schools and students' awareness levels should be increased.
Keywords: environmental health; microplastic; nursing; student; Turkey